Islamic Epistemology - Aswin Nasution; Asy'ari Asy'ari; Sri Handayani; Ridwan Ali (UM Purwokerto Press, 2023)
Humans have inquisitive nature and behavior, however differences in the quality and capacity of reason and knowledge have resulted in differences in the analysis of thought in finding the truth as epistemology. Epistemology which only emphasizes the ability of reason and senses, abandoning religion or God's revelation brings havoc to modern humans with a crisis of values and a life that is devoid of meaning. Islamic epistemology teaches God as the source of knowledge and truth while humans are the center, where religion or God's revelation as a source of absolute knowledge and truth can be obtained through (1) Al-Quran; (2) Hadith; (3) five senses; (4) Intellect; and (5) Qalb or heart. The solution to world problems that are so complex requires an Islamic epistemological, because Islam which originates from the revelation of Allah SWT has guaranteed its truth as a true guide to life.